2004
DOI: 10.1007/s00013-003-4780-3
|View full text |Cite
|
Sign up to set email alerts
|

Upper bounds for prime k -tuples of size log N and oscillations

Abstract: We prove the estimatefor the number E k (N ) of k-tuples (n + a 1 , . . . , n + a k ) of primes not exceeding N , for k of size c 1 log N and N sufficiently large. A bound of this strength was previously known in the special case n − 2 i (1 i < log n log 2 ) only, (Vaughan, 1973). For general a i this is an improvement upon the work of Hofmann and Wolke (1996).The number of prime tuples of this size has considerable oscillations, when varying the prime pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the case of primes, it may be the case that (1.16) fails when |H| > log x log 2 x owing to potentially large fluctuations in both the size of S(H) and in the prime counts themselves. We note that Elsholtz [8] has shown that for any c > 0, the left side of (1.16) is bounded by…”
Section: Background and Further Remarksmentioning
confidence: 88%
See 1 more Smart Citation
“…In the case of primes, it may be the case that (1.16) fails when |H| > log x log 2 x owing to potentially large fluctuations in both the size of S(H) and in the prime counts themselves. We note that Elsholtz [8] has shown that for any c > 0, the left side of (1.16) is bounded by…”
Section: Background and Further Remarksmentioning
confidence: 88%
“…when |H| c log x, where the implied function o(1) depends on c. On the other hand, there are admissible tuples with |H| log x for which the left side of (1.16) is zero (see [8] for a construction of such H).…”
Section: Background and Further Remarksmentioning
confidence: 99%
“…We now bound |Y a | from above using the following result by Elsholtz [2], which is based on the large sieve.…”
Section: Primesmentioning
confidence: 99%